Distribution and aetiology of blindness and visual impairment in mesoendemic onchocercal communities, Kaduna State, Nigeria. Kaduna Collaboration for Research on Onchocerciasis. Issue 1 (January 1994) - Abiose, A; Murdoch, I; Babalola, O; Cousens, S; Liman, I; Onyema, J; Evans, J; Gregory, W; Jones, B
Abstract : During a field trial of ivermectin in Kaduna State, 6831 people age 5 years and above, living in 34 mesoendemic onchocercal communities in Kaduna State, northern Nigeria, were examined for ocular disease. Visual function assessments included tests of visual acuity and visual fields. A total of 185 individuals (2.7%) were bilaterally blind by acuity criteria with a further 28 blind by field constriction. The overall prevalence of blindness was 3.1%. A further 118 individuals were visually impaired by WHO criteria. Examination for the cause of blindness revealed that 43% of eyes in bilaterally blind patients were blind due to onchocerciasis. A further 11% were blind from optic atrophy much of which was probably onchocercal in origin. Glaucoma was the next most common cause of blindness in the bilaterally blind (11%). Only 6% of eyes were blind from cataract as the primary cause. In the visually impaired population cataract was the most common primary cause of impaired/blind eyes (31%), followed by onchocerciasis (19%) [corrected].